2009
DOI: 10.1142/s0218127409025006
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Dislocation Density in Aluminum With Resonant Ultrasound Spectroscopy

Abstract: Dislocations in a material will, when present in enough numbers, change the speed of propagation of elastic waves. Consequently, two material samples, differing only in dislocation density, will have different elastic constants, a quantity that can be measured using Resonant Ultrasound Spectroscopy. Measurements of this effect on aluminum samples are reported. They compare well with the predictions of the theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…As briefly reported in [51], attempts to fit resonant frequencies assuming homogeneity and isotropy fail considerably. In fact, under the assumption of isotropy, measurements of matrix has five independent values.…”
Section: B Resonant Ultrasound Spectroscopymentioning
confidence: 99%
“…As briefly reported in [51], attempts to fit resonant frequencies assuming homogeneity and isotropy fail considerably. In fact, under the assumption of isotropy, measurements of matrix has five independent values.…”
Section: B Resonant Ultrasound Spectroscopymentioning
confidence: 99%
“…In this respect, some researchers [5,15,16] have investigated density of dislocations by ultrasound waves and have proposed some relationships between dislocation density and changes in the speed of elastic waves propagation. Sablik and Landgraf [17,18], Kobayashi et al [19], and Yaegashi [20] reported some relationships between dislocation density and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity of acoustic waves has a negative dispersion at low frequencies and then increases as a function of frequency around ω BP . Notice that the defects have an effect even at low frequencies, suggesting the model can be tested, say, using Resonant Ultrasound Sectroscopy (RUS), a tool that has been used to measure dislocation densities in polycrystalline materials [59,60], or hyper sound damping in the subteraherz range, as measured in vitreous silica [61,62]. Additional possible topics for further research include a numerical, atomistic, study of the hypothesized linear defects; the effect they would have on thermal and electrical conductivity properties, particularly at very low temperatures where quantum effects would be dominant; and the role they may or may not have in plasticity properties and in the glass transition.…”
Section: Figmentioning
confidence: 99%